Design and Analysis of Consequent-Pole Permanent Magnet Vernier Motor With Cancellation of Even-Order Harmonics - Hsieh, Min-Fu; Chang, Chia-Yuan; Huynh, Thanh-Anh; Dorrell, D. G. (IEEE Transactions on Magnetics, 2023)
This article develops a method for the cancellation of the inherent even-order harmonics in consequent-pole permanent-magnet vernier motors (CP-PMVMs) to improve the performance. Vernier motors can achieve high torque density; however, their high pole number means a high amount of rare-earth permanent magnet (PM) usage at a high cost. The consequent-pole design can reduce PM material cost but leads to high even-order harmonics and torque ripple. This article analyzes two winding configurations in order to develop the method for even-order harmonics cancellation in the CP-PMVMs. Two CP-PMVMs with different slot–pole combinations are analyzed to verify the proposed method. The effect of magnetic barriers on the torque output of the CP-PMVM with canceled even-order harmonics is evaluated. Finally, a multi-objective genetic algorithm is used to optimize the motor. Finite element analysis (FEA) is used to validate the design, with subsequent confirmation of simulations through prototype testing.
Keywords: Consequent pole; Electric vehicle (EV); Even-order harmonic; Green transportation; Optimization; Vernier motor; SDG-17: Partnerships for the goals